Implementation of School Management Information Systems at Vocational School State I Tomohon - Kamu, Israel Yonatan Fredrik; Rompas, Parabelem Tinno Dolf; Parinsi, Mario Tulenan (International Journal of Information Technology and Education, 2023)
This research discusses the implementation of the School Management Information System (SIMS) at SMK Negeri 1 Tomohon using the Rapid Application Development (RAD) method. School management, as a process of planning, organizing, directing, and controlling, is carried out by the school principal and his staff to achieve educational goals. The main goal of school management is to create an effective and efficient learning environment. Information systems, as entities with human, hardware, software, procedures, and data components, aim to collect, store, process, manage, and convey relevant information. SMK Negeri 1 Tomohon, as a vocational school in North Sulawesi, faces management challenges due to the use of conventional systems. Processes such as recording grades, registering students, compiling schedules, and collecting data on school fee payments often take time and are difficult. Therefore, this research is focused on implementing a School Management Information System using the programming languages PHP, HTML, CSS, and MySQL, with users consisting of Admin, Teachers, and Students, and using the RAD method. This research identifies problems in data management and school administration which are still manual, resulting in inefficiencies and potential errors. SIMS succeeded in making a positive impact with a structured interface, allowing easy access to information on grades, schedules, and learning activities. SIMS also facilitates systematic monitoring of student and teacher performance. This research concludes that SIMS can be an effective solution to support educational management at SMK Negeri 1 Tomohon with the potential for wider application in other school environments.